2004
DOI: 10.7601/mez.55.77_1
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance profiles and possible underlying mechanisms in German cockroaches, Blattella germanica(Linnaeus)(Dictyoptera: Blattellidae) from Peninsular Malaysia

Abstract: Insecticide resistance profiles and possible underlying mechanisms in German cockroaches, Blattella germanica (Linnaeus) (Dictyoptera: Blattellidae) from Peninsular Malaysia Leng-ChoyLEEi)' 2) and Chow-Yang LEEi)・ 3)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
2
25
0
3
Order By: Relevance
“…Our Þndings are comparable with those of Lee et al (1996a) and Lee and Lee (2004), who reported that propoxur resistance in the majority of German cockroach strains from Peninsular Malaysia was primarily due to elevated P450 monooxygenases and esterases. Lee and Lee (2004) also reported that altered acetylcholinesterase was involved in propoxur resistance in several Þeld strains of German cockroach from Peninsular Malaysia, as the resistance levels were only partially suppressed with PBO and DEF.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our Þndings are comparable with those of Lee et al (1996a) and Lee and Lee (2004), who reported that propoxur resistance in the majority of German cockroach strains from Peninsular Malaysia was primarily due to elevated P450 monooxygenases and esterases. Lee and Lee (2004) also reported that altered acetylcholinesterase was involved in propoxur resistance in several Þeld strains of German cockroach from Peninsular Malaysia, as the resistance levels were only partially suppressed with PBO and DEF.…”
Section: Resultssupporting
confidence: 93%
“…Previously, Scharf et al (1999) demonstrated that overexpression of P450 monooxygenases was well correlated with chlorpyrifos resistance in B. germanica. The involvement of microsomal oxidases and hydrolases in chlorpyrifos resistance also has been documented in several strains of German cockroach (Siegfried and Scott 1992, Hemingway et al 1993, Lee and Lee 2004. A more detailed synergism study on chlorpyrifos resistance is warranted to further substantiate the current observation.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…Bila mengacu kepada pengelompokan rasio resistensi yang disusun oleh Lee & Lee (2004), maka semua strain yang diperoleh dari lapangan termasuk pada kategori resisten tinggi (nilai RR 50 > 10). Tingginya tingkat resistensi terhadap permetrin kemungkinan disebabkan karena permetrin telah digunakan secara luas sejak tahun 1980an, baik untuk pengendalian hama pertanian, Terjadinya peningkatan resistensi akibat seleksi dari waktu ke waktu sampai pada lima generasi hingga 17,8 kali nampaknya karena insektisida telah menyeleksi individu rentan, dan yang berhasil hidup adalah individu yang resisten terhadap insektisida.…”
Section: Pembahasanunclassified